Estimating the sensitivity and specificity of serum ELISA and pooled and individual fecal PCR for detecting Mycobacterium avium subspecies paratuberculosis in Canadian cow-calf herds using Bayesian latent class models - Johnson, Paisley; McLeod, Lianne; Campbell, John; Rousseau, Marjolaine; Larson, Kathy; Waldner, Cheryl (Frontiers in Veterinary Science, 2022)
While Johne’s disease (JD) is less common in beef than in dairy herds, consolidation is increasing transmission risk. Estimates of Mycobacterium avium spp. paratuberculosis (MAP) prevalence and test performance in cow-calf herds are needed to inform control programs. Objectives of this study included describing the prevalence of MAP in Canadian cow-calf herds and comparing the relative performance of a serum ELISA, pooled fecal PCR and individual fecal PCR using Bayesian latent class models, and to investigate factors associated with positive MAP tests. Blood and fecal samples (n=3171) were collected from 159 Canadian cow-calf herds. All samples were analyzed using serum ELISA and fecal PCR (pools of five samples) and a subset of 913 fecal samples were also tested with individual PCR. Based on latent class analysis, MAP prevalence was higher in eastern compared to western Canada for both animals (East, 3% [95% Credible Interval (CrI) 1-7%]; West, 1% [95% CrI 0.2-2%]) and herds (East, 15% [95% CrI 2-35%]; West, 10% [95% CrI 1-26%], based on one or more positive results). Sensitivity (Se) and specificity (Sp) for animal level individual PCR were 96% (95% CrI 80-100%) and 98% (95% CrI 96-100%) respectively followed by pooled PCR (Se=54% [95% CrI 36-72%]), Sp≥99.9% [95% CrI 99.8-100%]) and ELISA (Se=36% [95% CrI 22-52%], Sp=98% [95% CrI 96-99%]). Based on 20 samples per herd, the herd level Se of ELISA was 79% (95% CrI 47-100%) (at least one positive sample) compared to 43% (95% CrI 14-94%) for pooled PCR. Herd-level Sp was 99% (95% CrI 96-100%) for pooled PCR and 90% (95% CrI 83-100%) for ELISA. Cows from herds with dairy cattle on farm and cows with symptoms of JD in the past three years were more likely to be MAP positive. Herds that had animals with JD symptoms in the previous three years and those with more breeding females were most likely to test positive for MAP. While serum ELISA can be effective for herd screening, PCR performed better for animal testing. Pooled PCR testing could be a less costly option; however, determining the most cost-effective approach will require further economic analysis.